2023
DOI: 10.1002/ijc.34543
|View full text |Cite
|
Sign up to set email alerts
|

China special issue on gastrointestinal tumors‐Improved survival after multidisciplinary team decision for patients with advanced gastrointestinal cancer: A multicenter, noninterventional, controlled study

Abstract: Formal multidisciplinary team (MDT) discussions in clinical practice require time and space but have unclear survival benefits for advanced gastrointestinal cancer patients. Our study aimed to investigate the long‐term survival of patients with advanced gastrointestinal cancer after MDT decision. From June 2017 to June 2019, continuous MDT discussions on advanced gastrointestinal cancer were conducted in 13 medical centers in China. MDT decisions and actual treatment received by patients were prospectively rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Extensive evidence supports the impact of MDT processes on patient survival, demonstrating improved OS under MDT care[ 40 , 41 ]. Notably, a Chinese study reported that MDT discussions contributed to prolonged OS in patients with advanced gastrointestinal cancers, including CRC[ 42 ]. Additionally, preoperative MDT assessment has shown associations with enhanced survival in patients with locally advanced colon cancer[ 43 ].…”
Section: The Crucial Role Of Mdt In Customizing Individualized Approa...mentioning
confidence: 99%
“…Extensive evidence supports the impact of MDT processes on patient survival, demonstrating improved OS under MDT care[ 40 , 41 ]. Notably, a Chinese study reported that MDT discussions contributed to prolonged OS in patients with advanced gastrointestinal cancers, including CRC[ 42 ]. Additionally, preoperative MDT assessment has shown associations with enhanced survival in patients with locally advanced colon cancer[ 43 ].…”
Section: The Crucial Role Of Mdt In Customizing Individualized Approa...mentioning
confidence: 99%
“…Multidisciplinary management has significantly extended the survival of patients with rectal cancer, increasing the number of rectal cancer survivors (1)(2)(3). Subsequently, the problem of chronic cardiovascular disease is also highlighted in these survivors, who are more predisposed to developing cardiovascular disease (CVD) than those without a history of cancer (4,5).…”
Section: Introductionmentioning
confidence: 99%